MathCAD 7 student edition getting started
Mathcad is a rich problem-solving environment that gives you a wide choice of tools and supports a variety of analysis and visualization techniques. Even experienced Mathcad users constantly discover new ways of using Mathcad, and for the beginner the possibilities can be overwhelming. To get you started we've assembled an overview of Mathcad's features. This should orient you in Mathcad's problem solving space and give you a taste of the Mathcad way of doing things. Then we'll point you toward the wealth of resources available on-line within Mathcad and on the Internet.